2019
DOI: 10.1016/j.ajhg.2019.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic Mutations in TTC29 Cause Male Subfertility with Asthenoteratospermia in Humans and Mice

Abstract: As a type of severe asthenoteratospermia, multiple morphological abnormalities of the flagella (MMAF) are characterized by the presence of immotile spermatozoa with severe flagellar malformations. MMAF is a genetically heterogeneous disorder, and the known MMAFassociated genes can only account for approximately 60% of human MMAF cases. Here we conducted whole-exome sequencing and identified bi-allelic truncating mutations of the TTC29 (tetratricopeptide repeat domain 29) gene in three (3.8%) unrelated cases fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 65 publications
2
54
1
Order By: Relevance
“…At least 19 additional genes, including AK7 , ARMC2 , CFAP43/44 , CFAP69 , FSIP2 , QRICH2 , DNAH17 , TTC21A , WDR66 , CEP135 , TTC29 , CFAP65 , and DNAH8 and so forth, have been reported mutated in patients with MMAF, 9,10 showing the high‐genetic heterogeneity of this phenotype. Nevertheless, it is estimated that the causes for approximately 50% of MMAF patients remain unknown, 11,12 suggesting that more genetic factors and the underlying mechanism need to be explored to completely understand the pathogenesis of MMAF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 19 additional genes, including AK7 , ARMC2 , CFAP43/44 , CFAP69 , FSIP2 , QRICH2 , DNAH17 , TTC21A , WDR66 , CEP135 , TTC29 , CFAP65 , and DNAH8 and so forth, have been reported mutated in patients with MMAF, 9,10 showing the high‐genetic heterogeneity of this phenotype. Nevertheless, it is estimated that the causes for approximately 50% of MMAF patients remain unknown, 11,12 suggesting that more genetic factors and the underlying mechanism need to be explored to completely understand the pathogenesis of MMAF.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is estimated that the causes for approximately 50% of MMAF patients remain unknown, 11,12 suggesting that more genetic factors and the underlying mechanism need to be explored to completely understand the pathogenesis of MMAF.…”
mentioning
confidence: 99%
“…These mutations generate isolated male infertility associated with severe asthenozoospermia in the absence of any other pathology and are known collectively as Multiple Morphological Abnormalities of the sperm Flagella (MMAF). The list of mutations responsible for MMAF is expanding rapidly but currently includes mutations in adenylate kinase 7 ( AK7 ) ( 36 ), glutamine rich 2 ( QRICH2) ( 37 ), cilia and flagella associated proteins ( CFAP43, CFAP44, CFAP65, CFAP69, CFAP70, CFAP91, CFAP251 ) ( 38 44 ) WD repeat domain 19 ( WDR19 ) ( 45 ), DAZ interacting zinc finger protein ( DZIP1 ) ( 46 ), DNAH1 (also implicated in PCD) ( 47 ) DNAH2 ( 48 ), DNAH6 ( 49 ), DNAH17 ( 50 ), TTC29 ( 51 ), TTC21A ( 52 ), armadillo repeat containing 2 ( ARMC2 ) ( 53 ) CEP135 (centrosomal protein 135) ( 54 ). fibrous sheath interacting protein 2 ( FSIP2 ) ( 55 ), ADP ribosylation factor like GTPase 2 binding protein ( ARL2BP ) ( 56 ), sperm flagellar 2 ( SPEF2 ) ( 57 ), and DnaJ heat shock protein family ( Hsp40 ) member B13 ( DNAJB13 ) ( 58 ).…”
Section: Genetic Causes Of Male Infertilitymentioning
confidence: 99%
“…Previous studies have identified several flagella-associated genes, including AKAP3, AKAP4, TTC21A, TTC29, FSIP2, DNAH1, DNAH2, DNAH6, DNAH8, DNAH17 , and DZIP1 , that are involved in sperm flagellum biogenesis (Ben Khelifa et al, 2014; Y. Li et al, 2019; C. Liu et al, 2019; C.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al, 2019; C. Liu et al, 2020; W. Liu et al, 2019; Lv et al, 2020; Martinez et al, 2018; Sha, Wei, et al, 2020; Tu et al, 2019; Turner et al, 2001).…”
Section: Introductionmentioning
confidence: 99%